PENGARUH KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DENGAN CSR SEBAGAI VARIABEL MODERASI - Nursasi, Enggar (JURNAL AKUNTANSI DAN INVESTASI, 2020)
This research aims to analyze the effect of Financial Performance on Company Value and Analyze the role of Corporate Social Responsibility as a moderating variable in the effect of Financial Performance on Company Value on mining companies listed on the Stock Exchange for 2016-2018. The sampling technique in this study is the purposive sampling method and the MRA (Moderated Regression Analysis) Test is the data analysis used in this study. The model test results showed an R square value of 87.2%, so it can be concluded that the research model has a good match with the data. This means that the variable performance and CSR as a moderating have a good ability to predict variations in value on the company's value variable.            Hypothesis test results concluded that financial performance variables statistically have a positive and significant effect on firm value. While CSR is also statistically proven to have a negative moderating effect on firm value.